The myth of the flat start‐up: Reconsidering the organizational structure of start‐ups - Lee, Saerom (Ronnie) (Strategic Management Journal, 2022)
Research summary There has been an ongoing debate over whether start‐ups should be “flat” with minimal hierarchical layers. To reconcile this debate, this article distinguishes between creative and commercial success (i.e., novelty vs. profitability), and examines how these outcomes are variously influenced by a start‐up's hierarchy. This study suggests that while a flatter hierarchy can improve ideation and creative success, it can result in haphazard execution and commercial failure by overwhelming managers with the burden of direction and causing subordinates to drift into power struggles and aimless idea explorations. I find empirical support for this trade‐off using a large sample of game development start‐ups. These findings offer one resolution to the debate by sorting out the conditions under which hierarchy can be conducive or detrimental to start‐ups. Managerial summary Academics, management gurus, and popular media outlets have argued that “authoritarian,” tall hierarchies are outmoded and will be supplanted by “egalitarian,” flat structures. In recent years, this argument has been largely substantiated by a few “successful” flat start‐ups, such as Valve, Zappos, Github, Medium, and Buffer. As these nascent firms constantly garner much attention for their egalitarian ideal—which itself is a signal of their rarity—the myth that start‐ups should be flat (often referred to as “flat organization,” “holacracy,” or “boss‐less firm”) has become widespread among entrepreneurs. My study cautions against this myth, suggesting that adding a few hierarchical levels of managers can substantially help start‐ups achieve commercial success and survive in their hostile environments, albeit at a potentially marginal cost of creativity.